MANAJEMEN PERUBAHAN DI PEMERINTAH DAERAH PROVINSI SULAWESI TENGAH - DEWI BUNTUANG, PRICYLIA CHINTYA (Fakultas Ekonomi Universitas Tadulako, 2016)
This study aims to know and analyze of the description implementation of change management in Central Sulawesi Provincial Government. The method used in this research is descriptive. This research was conducted at work unit of local government area of Central Sulawesi Province with unit of employee analysis. . Data were obtained using observation, questionnaire and documentation. The sample of the study amounted to 308 respondents determined by stratified random sampling technique. The results show that the implementation of change management in the Central Sulawesi Provincial Government has been implemented based on the model developed by Kurt Lewin which consists of unfreezing, changing and refreezing, where the research results show that the most influential aspect in shaping change management in Central Sulawesi Province is the refreezing aspect which states that employees create / maintain change, while the weakest aspect in influencing change management is unfreezing caused employees are less ready to face changes even employees less open themselves to changes made by the organization in this case the unit of work area .